Gender Language Differences Founded in RANS Entertainment Podcast - Asya, Shafira; Fanisa, Naza; Clarissa, Cindy; Rangkuti, Rahmadsyah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2023)
This research mainly to identify language contrast used by male and female on Raffi Ahmad and Nagita Slavina podcast video in RANS entertainment youtube channel. The theory used in this research is the differences between male and female language use in the form of six contrasts by Deborah Tannen (1990). The research method used is qualitative method. The results showed that the way of male speaking, the writers get 7 status, 1 independency, 2 advice, 1 information, 1 orders, and 9 conflict. On the other hand, for the way of female speaking, the writers get 1 support, 1 understanding, 4 feelings, 1 proposal, and 3 compromise. The writers didn’t get intimacy from female in this podcast video between Raffi and Nagita.